2014
DOI: 10.1186/s40677-014-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

The 21 February 2005, catastrophic waste avalanche at Leuwigajah dumpsite, Bandung, Indonesia

Abstract: International audienceOn 21 February 2005 the Leuwigajah dumpsite, Bandung (Java, Indonesia) was affected by a largeslide after heavy rainfalls. Second deadliest waste slide in history, it buried 71 houses and killed 143 people.Amongst the contemporary disastrous events of this type, only a few have been documented. We explored failurepreconditions, triggering mechanisms and local context that conducted to this disaster. We carried on four fieldinvestigations on the site. A series of aerial photographs were ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 16 publications
0
32
0
1
Order By: Relevance
“…Heavy rainfall (Merry et al, 2005) is another cause. The accumulation of landfill gas (Lavigne et al, 2014) and landfill plastic both also cause an increase in leachate level (Blight, 2008). A high leachate level in the landfill will increase the pore water pressure and reduce the shear strength parameters of the MSW, affecting the stability of the landfill.…”
Section: Landfill Instability Case Studiesmentioning
confidence: 99%
“…Heavy rainfall (Merry et al, 2005) is another cause. The accumulation of landfill gas (Lavigne et al, 2014) and landfill plastic both also cause an increase in leachate level (Blight, 2008). A high leachate level in the landfill will increase the pore water pressure and reduce the shear strength parameters of the MSW, affecting the stability of the landfill.…”
Section: Landfill Instability Case Studiesmentioning
confidence: 99%
“…Meteorological conditions were scored medium-low risk, however the evidence is lacking to assess the prevalence of harm from these hazards. (Blight, 2008;Jayaweera et al, 2019;Lavigne et al, 2014;Nikulishyn et al, 2020;Xu et al, 2017;Yin et al, 2016).  These incidents impact local area swamping land, destroying houses and ruining communities.…”
Section: Risk Characterisation For Meteorological and Geophysical Hazmentioning
confidence: 99%
“…On mass, piles of waste can also have catastrophic consequences if they become unstable (Lavigne et al, 2014). There have been multiple incidents over recent decades that have resulted in the deaths of many hundreds of people who work on dumpsites or live nearby (Blight, 2008;Lavigne et al, 2014;Yoshida, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Landfill slope failure at MSW dumpsites can be found in previous studies, wherein six reported cases between 1993 and 2005 resulted in approximately 500 deaths and significant economic loss (Blight, 2008;Blight and Fourie, 2005;Eid et al, 2000;Kjeldsen and Fischer, 1995;Kocasoy and Curi, 1995;Merry et al, 2005;Mitchell et al, 1990). The deadliest event in history killed 278 people in Manila, Philippines, in 2000, and the second deadliest event killed 143 people and buried 71 houses on 21 February 2005 at the Leuwigajah dumpsite near Bandung, Indonesia (Lavigne et al, 2014).…”
Section: Introductionmentioning
confidence: 99%